Deformasi Permanen dan Modulus Resilien Campuran AC-BC Modified Menggunakan Aspal Multigrade - Desy Yofianti (Universitas Islam 45, 2019)
Multigrade asphalt use is an alternative method for handling road deterioration problem, e.g. a rutting, due to the repetitive traffic load and high pressure from vehicle wheels. In addition, the multigrade asphalt has been widely used to reduce temperature sensitivity of the asphalt mixture in flexible pavement due to an unpredictable climate change. Rutting is also caused by the accumulation of permanent deformations from all layers in the pavement structure. This study aims to analyze the permanent deformation value and the resilient modulus of an Asphalt Concrete Binder Course (AC-BC) modified mixture through the use of multigrade asphalt. The Wheel Tracking Test and UMATTA Test were used to test the specimens. The Tests on samples were carried out at temperatures of 35oC and 50oC. The results showed that the permanent deformation value of the AC-BC with multigrade asphalt had a better deformation resistance than the 60/70 pen bitumen mixture at 35oC. At the temperature of 50oC, the multigrade asphalt mixture had a smaller permanent deformation value (0.92 mm) compared to the 60/70 pen bitumen mixture. At the temperature of 35oC, multigrade asphalt mixture had a resilient modulus value of 1.04 times greater than the 60/70 pen bitumen mixture and at the temperature of 50oC, this mixture had a resilient modulus value of 1.16 times greater than the 60/70 pen bitumen mixture. Therefore, this study concluded that the increase/decrease of value of permanent deformation and resilient modulus were influenced by the temperature and types of asphalt in the mixture.